Chalcone Derivatives with Cyclooxygenase Inhibiting Activity - Tambago, Gian Carlo; Amor, Evangeline C. (Science Diliman: A Journal of Pure and Applied Sciences, 2022)
Dimethylcardamonin (DMC) or (E)-2’,4’-dihydroxy-6’-methoxy-3’,5’-dimethyl chalcone was isolated from  Syzygium samarangense  (Blume) Merr. leaves using vacuum liquid chromatography and normal phase silica-gel column chromatography. DMC was purified from the fraction that eluted out of 9:1 (v/v) hexane: ethyl acetate to 7:3 (v/v) hexane: ethyl acetate. Using a modified method from Geissman (1948), DMC was derivatized via alkaline peroxidation from which compounds A and B were obtained. Compound A was identified to be (2S)-7- hydroxy-5-methoxy-6,8-dimethyl flavanone (C18H18O4 ) while B had a methoxy group on its 4’ position instead of a hydroxyl group with respect to DMC. The flavanone derivative may have been formed due to substituent effects on the ring. DMC, A, and B were tested for their inhibitory activity against cyclooxygenase enzymes at 10 and 100 ppm. A and B gave at least 50% inhibitory activity at 100 ppm and were found to be COX-2 selective inhibitors. DMC was inactive at both 10 and 100 ppm.